2009
DOI: 10.1111/j.1365-2583.2009.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and influences of classical insect hormones on the expression profiles of a molting carboxypeptidase A from the cotton bollworm (Helicoverpa armigera)

Abstract: Molting is a very important physiological behavior to arthropods. During molting, integument apolysis occurs, which is the digestion and absorption of the old endocuticle for new cuticle formation. Proteases play critical roles in this process. Molting carboxypeptidase A ( Ha-CPA ) is characterized from Helicoverpa armigera . The Ha-CPA transcript was mainly present in the integument from the 5th instar larvae. In the integument, the transcription level of the gene reached its peak at the 5th instar molting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…CPA is also highly expressed during metamorphosis in H. armigera (Sui et al, 2009); therefore, FoxO could also regulate metamorphic molting. However, any effect of FoxO knockdown on metamorphic molting could not be examined in our study because the larvae died before metamorphosis after FoxO knockdown in fifth instar larvae.…”
Section: Foxo Via Brz7 Mediates Cpa Expression For Insect Moltingmentioning
confidence: 99%
See 2 more Smart Citations
“…CPA is also highly expressed during metamorphosis in H. armigera (Sui et al, 2009); therefore, FoxO could also regulate metamorphic molting. However, any effect of FoxO knockdown on metamorphic molting could not be examined in our study because the larvae died before metamorphosis after FoxO knockdown in fifth instar larvae.…”
Section: Foxo Via Brz7 Mediates Cpa Expression For Insect Moltingmentioning
confidence: 99%
“…CPA in the molting fluid participates in apolysis and its transcript levels are increased at the fifth instar molting stage and the sixth instar prepupal stage by 20E induction in H. armigera (Sui et al, 2009). The present study showed that FoxO knockdown leads to molting failure because of the suppression of BrZ7 and CPA expression.…”
Section: Foxo Via Brz7 Mediates Cpa Expression For Insect Moltingmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentrations were analyzed according to the Bradford method (Bradford, 1976) using bovine serum albumin as the standard. Western blot was performed according to a previously described method (Sui et al, 2009). …”
Section: Western Blottingmentioning
confidence: 99%
“…The purified HaBBP was used as the antigen for producing polyclonal antiserum according to a previously described method (Sui et al, 2009).…”
Section: Recombinant Expression and Antiserum Preparationmentioning
confidence: 99%